Functionalization of alkynes and alkenes using a cascade reaction approach: synthesis of beta-keto sulfones under metal-free conditions - Kumar, Mukesh; Ahmed, Riyaz; Singh, Maninder; Sharma, Shweta; Thatikonda, Thanusha; Singh, Parvinder Pal (Journal of Organic Chemistry, 2020)
Here, we are reporting a multicomponent cascade reaction approach for the synthesis of beta-keto sulfones by exploiting differential reactivity pattern of substrates under open-atmosphere and metal-free conditions. The coupling partners are aryldiazonium salts, unsaturated compounds, and DABSO. The optimized conditions worked well with both alkenes and alkynes. Moreover, the reaction also works with metabisulfite for the source of sulfone. The controlled liquid chromatography-mass spectrometry and O-18-labelled experiments suggested that air is a source of the incoming oxygen atom of the keto group of beta-keto sulfones.

Sulfonyl pyrazoles as sustainable dual functional group transfer reagents: AlCl3 promoted transfer of sulfonyl and pyrazole groups - Kour, Harpreet; Mahajan, Shivangani; Ahmed, Sumeer; Birajdar, Ram; Verma, Praveen Kumar; Singh, Parvinder Pal; Sawant, Sanghapal D. (Journal of Organic Chemistry, 2026)
Herein, we report sulfonyl pyrazoles as sustainable dual-functional group transfer reagents for the transfer of two different functional groups to two different acceptors under mild conditions facilitated by AlCl3. The transformation proceeds via two distinct transition states: in the first, AlCl3 activates the S-N bond toward cleavage, and in the second, a sulfoximine nucleophilically attacks the sulfonyl group, resulting in the elimination of the pyrazole moiety. This process yields sulfonyl amidines, compounds with significant medicinal relevance, while the liberated pyrazole effectively participates in subsequent reactions with Michael acceptors. Notably, the protocol operates without the need for transition-metal catalysts and exhibits broad substrate scope along with excellent functional group tolerance.